Diagnostic value of procalcitonin in patients with periprosthetic joint infection: a diagnostic meta-analysis - Sun, Xiaobo; Li, Yijin; Lv, Yan; Liu, Yuting; Lai, Zhiwei; Zeng, Yirong; Zhang, Haitao (Frontiers in Surgery, 2024)
The success rate of periprosthetic joint infection (PJI) treatment is still low. Early diagnosis is the key to successful treatment. Therefore, it is necessary to find a biomarker with high sensitivity and specificity. The diagnostic value of serum procalcitonin (PCT) for PJI was systematically evaluated in this paper. It will provide the theoretical basis for clinical diagnosis and treatment.We searched the Web of Science, Embase, the Cochrane Library, and Pubmed for studies that evaluated the diagnostic value of serum PCT for PJI (from the inception of each database until September 2020). Two authors independently screened the literature according to the inclusion and exclusion criteria. The quality of each selected literature was evaluated by using the QUADAS-2 tool. Revman 5.3 software was used for the quality evaluation. The sensitivity (SN), specificity (SP), positive likelihood ratio (PLR), negative likelihood ratio (NLR) and diagnostic odds ratio (DOR) were merged by using Meta-disc 1.4 software. The area under the curve (AUC) and Q index were calculated after the summary receiver operating characteristic (SROC) was generated. We also performed subgroup analysis.A total of 621 patients were enrolled in the nine studies. The pooled sensitivity of serum PCT for PJI diagnosis was 0.441 (95%CI, 0.384-0.500), the pooled specificity was 0.852 (95% CI, 0.811-0.888), the pooled PLR was 2.271 (95% CI, 1.808-2.853), the pooled NLR was 0.713 (95% CI, 0.646-0.786), and the pooled DOR was 5.756 (95% CI, 3.673-9.026). The area under SROC (the pooled AUC) is 0.76 (0.72-0.79).Q index is 0.6948.PJI is a low-toxic infection with low systemic inflammatory response in most cases. Therefore, local joint infection will not cause the increase of serum PCT unless the local infection becomes a systemic infection.The clinical value of serum PCT for PJI is not significant. Serum PCT was not suitable as a serum marker for PJI diagnosis.